A chiral “Siamese-Twin” calix[4]pyrrole tetramer - Galán, Albano (Royal Society of Chemistry, 2016)

(untitled) (Chem Sci)
We describe our results in the attempted template syntheses of oligomacrocycle calix[4]pyrrole dimer 4, using Hay coupling reaction conditions, tetraalkynyl calix[4]pyrrole 5 as starting material and two bipyridyl N-oxides of different length as templates. We found that the short bis-N-oxide 3 was not an efficient template for the macrocyclization reaction producing an insoluble crude reaction mixture containing exclusively oligomerization and polycondensation products. On the other hand, when we used the long bis-N-oxide 6 as template we obtained a soluble crude reaction mixture in which we did not detect the expected calix[4]pyrrole dimer 4. Instead, we isolated, in low yield, an encapsulation complex of the bis-N-oxide 6 in a partially reacted calix[4]pyrrole dimer. The major isolated species was an unprecedented calix[4]pyrrole tetramer encapsulating two molecules of 6. The complex adopted a chiral helical-like conformation in the solid state resembling the previously described so-called “Siamese-Twin porphyrins”.